Meaning and Mourning: The Search for Significance in Tragic Loss - Robert A. Neimeyer (Ewha Journal of Social Sciences, 2017)
The death of a significant person, especially when it comes tragically or prematurely, can shake the foundations of our assumptive and relational world and lead to anguished attempts to find meaning in the loss and in our lives in its aftermath. In this chapter I summarize what is known about complicated grief following difficult losses, review one program of research focused on this attempt at meaning reconstruction, describe recently developed measures of meaning in mourning, and discuss several therapeutic techniques for helping clients make sense of the death and rework their attachment relationship to the deceased. I conclude by illustrating some of this work in my therapy with a couple who had lost not one but two children to tragic accidents, as they tried to adapt to a compound traumatic bereavement. KCI Citation Count: 0